MEMBANGUN PARAMETER GENERASI EMAS BERBASIS KEUNGGULAN LOKAL DALAM UPAYA PENGEMBANGAN PENDIDIKAN INDONESIA - Ismira; Zulfahman Siregar; Evi Desmariani (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
Form a complete Indonesian man depicted in the description of the National Education Goals faithful, pious, virtuous, intelligent, skilled and healthy. Description of the National Education Goals can essentially be used as a parameter nationally desired generation born from the process of education in Indonesia. The 21st century is marked by the challenges of globalization in almost all sectors of life both in economics, culture, education, technology. Facing the challenges of the 21st century, we need a reliable human resources capable of critical thinking, moral good, skilled and intelligent collaboration. Indonesian Golden Generation is the generation of reliable and is expected to appear on the 100th anniversary of Indonesia's independence (2045) future. Desired Golden Generation is the generation that is able to compete internationally but mastering excellence Indonesia's natural resources in an attempt to survive the threat of globalization of the world. Therefore, it is necessary to develop parameters golden generation of local excellence in the development of education in Indonesia.